Fungal diversity and functionality are driven by soil texture in Taylor Valley, Antarctica. (April 2021) - Canini, F.; Geml, J.; D'Acqui, L.P.; Buzzini, P.; Turchetti, B.; Onofri, S.; Ventura, S.; Zucconi, L.
Abstract: The McMurdo Dry Valleys surface is mainly constituted from unconsolidated permafrost. Despite the combination of cold and dry conditions, transiently wetted soils close to lake edges are hotspots of intense biological activity, that can support the surrounding soil ecosystems in such extreme environments. These soils host simple microbial communities that allow easy characterization of the parameters determining microbial establishment and diversification. Soil samples were collected close to three different glacial lakes (Lake Fryxell, Lake Hoare and Lake Joyce) located along a longitudinal gradient from the lower to the upper Taylor Valley. Fungal diversity and functionality of sampled soils were studied through ITS1 metabarcoding sequencing. The correlation between the parameters describing fungal diversity (i.e. total richness, relative richness of dominant taxonomic and functional groups, and community composition) and the edaphic physicochemical parameters (i.e. pH, moisture, C, N, P, Na +, K +, Mg 2+ and Ca 2+, cation exchange capacity, and soil granulometry) was assessed. The fungal communities showed low richness (48 ± 32 OTUs per sample). Their composition was highly diversified even within different sites close to the same lake. The main parameters affecting the diversity and composition of fungal communities were soil texture, in turn influencing the retention of water and nutrients, and physicochemical properties. This is of particular concern for the survival of these communities, given the expected environmental changes due to global warming.